Penerapan Sistem Informasi Akuntansi Pada Pelayanan Apotek Pharm 24 Yogyakarta: Akuntansi; Laporan Keuangan; Pengolahan Data; Aplikasi; MYOB Premier V.16 - Mari Rahmawati; Winda Amelia (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2021)
Abstract The running of business activities, of course, requires important components such as accounting that determines whether the business is running smoothly or not. With accounting, business owners will know the possibilities that will happen in the future. To find out this possibility, companies need financial reports to obtain information about the company's losses or profits. However, there are still many business fields that have problems in presenting financial statements that are inaccurate and time-consuming. Based on this, the authors conducted research on the accounting data processing process at Pharm 24 Pharmacy which still uses manual recording where the authors make observations and interviews with the system at the Pharmacy, then the recording is applied to a computerized recording system using the MYOB Premier V. Accounting Application. 16. The purpose of this study is to determine the resulting accounting process after computerized processing of accounting data and then make comparisons with a manual accounting recording system. The results of this study can assist the Pharm 24 Pharmacy in processing their business accounting data to make it more effective and efficient in recording so that the resulting financial reports are more accurate. Keywords: Accounting; Financial statements; Data processing; Application; MYOB Premier V.16